2007 IEEE/SP 14th Workshop on Statistical Signal Processing 2007
DOI: 10.1109/ssp.2007.4301236
|View full text |Cite
|
Sign up to set email alerts
|

Encoding Neuroanatomical Information using Weighted Spherical Harmonic Representation

Abstract: Cortical surfaces can be modeled using the recently developed weighed spherical harmonic (SPHARM) representation. The weighted-SPHARM representation incorporates data smoothing, parametrization and surface registration in a unified mathematical framework. The weighted-SPHARM represents the surface coordinates as a weighted linear combination of spherical harmonics in such a way that it solves a heat equation. The representation can decomposes an arbitrary surface into symmetric and asymmetric parts with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Spherical harmonics have been extensively researched for the description of cortical surfaces (Fig. 8) [135,136,137]. An advantage of this representation is its robustness to noise when using lower frequency bands only, as noise is generally represented by higher frequencies.…”
Section: Descriptor Representationmentioning
confidence: 99%
“…Spherical harmonics have been extensively researched for the description of cortical surfaces (Fig. 8) [135,136,137]. An advantage of this representation is its robustness to noise when using lower frequency bands only, as noise is generally represented by higher frequencies.…”
Section: Descriptor Representationmentioning
confidence: 99%
“…The method is applicable to the prostate (39), and also to breast cancer tumor (40), liver (41), kidney (42), heart (43), cortical surface of brain (44), and possibly others. Evidently, only linear deformation and isotropic conditions have been investigated and in order for the method to be more flexible, nonlinear and anisotropic situations have to be included in the model.…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…Spherical Harmonics (SPHARM), a popular method of shape analysis, can be used to improve alignment accuracy and speed. Spherical harmonic analysis [131,132] considers 3D surface data as a linear combination of specific basis functions. Additionally, SPHARM provides a rotation invariant common coordinate system in which shapes can be analyzed.…”
Section: Spherical Harmonicsmentioning
confidence: 99%
“…The more coefficients used in the reconstruction, the more detail is present in the final constructed shape. Gerig et al [131], which have shown SPHARM as a potential method for classifying neurolog- [133] 1999 A 3D 21 N Gerig et al [131] 2001 A 3D 20 C Chung et al [132] 2007 A 3D 28 C Uthama et al [134] 2007 A 3D 40 C Abdallah et al [135] 2008 A 3D 18 C Chung et al [136] 2008 A 3D 28 C Uthama et al [137] 2008 A 3D 20 C Esmaeil-Zadeh et al [138] 2010 A 3D 95 N Nitzken et al [139] 2011 A 3D 45 C Nitzken et al [140] 2011 [142] 2011 A 3D n/a C Paniagua et al [86] 2013 A 3D 90 C Hosseinbor et al [143] 2013 A 3D 69 C ical disorders. SPHARM has been widely applied as a method for potential diagnosis.…”
Section: Spherical Harmonicsmentioning
confidence: 99%
See 1 more Smart Citation